Conservative Management of Reversible Total Atrioventricular Block Resulting in Sinus Rhythm Recovery: A Case Report - Eka Oktaviana Hirda; Nelly Mulyaningsih; Mohammad Sutami; Athaya Rahmanardi Muhammad (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
A 49-year-old woman presented with weakness, nausea, and vomiting and was found to have complete atrioventricular (AV) block on electrocardiography. Initial evaluation suggested hypovolemia and electrolyte disturbance due to poor oral intake, with mild hypokalemia identified as a potential reversible contributor to the conduction abnormality. Although temporary pacing was considered because of the severity of the AV block, the patient was managed conservatively with fluid resuscitation and potassium replacement after referral was declined by the family. Progressive clinical and electrocardiographic improvement was observed, with restoration of normal sinus rhythm by the sixth hospital day and complete resolution of symptoms. This case highlights the importance of identifying reversible causes before permanent pacemaker implantation.